Need Analysis of Virtual Lab in The Implementation of Academic and MBKM Policies - Suryandari, Suryandari; Khairunnisa, Khairunnisa; Destiara, Meyninda (Institut Agama Islam Negeri Palangka Raya, 2023)
A virtual laboratory is a simulation space that can be used in the teaching and learning process in a virtual environment. In this virtual space, the learning process allows for interaction and collaboration within groups. The advancement of the era in Society 5.0 has brought about differentiated learning models that adjust to students' characteristics. Furthermore, the development of innovative learning methods has become more modified. This innovation should be based on an analysis of the needs for learning creativity, one of which is the innovation of learning using a virtual laboratory. The learning process in the laboratory requires activities such as observing, investigating, and interpreting data. This research is a qualitative descriptive study using interviews, questionnaires, literature studies, and observations. The research data indicate that the virtual laboratory has met the urgency points to be developed as a learning medium at various educational levels, both offline and online. In accordance with the needs of the Society 5.0 era, the MBKM policy, as well as the teaching implementation standards at UIN Antasari Banjarmasin, the virtual laboratory has proven to be necessary and capable of serving as an implementation space. A key consideration in using the virtual laboratory is the management of the virtual laboratory, which can be regulated in academic policy documents ranging from guidelines, procedures, to forms and virtual laboratory modules.